Engagement in athletic career: A study of female Brazilian handball world champions - Lima, L. A. D.; Reverdito, R. S.; Scaglia, A. J.; Galatti, L. R. (International Journal of Sports Science and Coaching, 2023)
The aim of this study was to identify and describe elements that influenced the engagement of the 2013 Brazilian handball female world champions from grassroots to elite sports levels. Seven members of the team participated in a retrospective examination of their athletic development, with a mean of 20 years of sports experience. A semi-structured interview and questionnaire were used for data collection, and the script was based on the development stages of the Developmental Model of Sport Participation and the dynamic elements of the Personal Assets Framework. The thematic analysis showed that the athletes` personal characteristics, their disparate environments, and the quality of their relationships were significant in their pathway to elite performance. The results show that well-structured settings are not important in the early years, but rather the coaches` interest in keeping young athletes engaged in sport is one of the key elements. Moreover, the advance in the maintenance years, training in a more structured setting and the coaches` caring attitude and attention to their athletes` feelings and emotions can lead to pathways toward excellence.